Syndecans in Inflammation at a Glance - Gopal, Sandeep (Frontiers in Immunology, 2020)
Syndecans are transmembrane proteoglycans with heparan and chondroitin sulfate chains attached to their extracellular domain. Like many proteoglycans, they interact with a large number of ligands such as growth factors, adhesion receptors, soluble small molecules, proteinases and other extracellular matrix proteins to initiate downstream signaling pathways. Syndecans play a major role in inflammation, mainly by regulating leukocyte extravasation and cytokine function. Conversely, syndecans undergo cytokine mediated changes in their expression levels during inflammation. The function of syndecans during inflammation appears to depend on the stage of inflammation, heparan/chondroitin sulfate chains, the rate of ectodomain shedding and the solubility of the ectodomains. From the current literature, it is clear that syndecans are not only involved in the initial recruitment of pro-inflammatory molecules but also in establishing a balanced progression of inflammation. This review will summarize how cell surface and soluble syndecans regulate multiple aspects of inflammation